2021
DOI: 10.1016/j.pmedr.2021.101529
|View full text |Cite
|
Sign up to set email alerts
|

Testing positive for Human Papillomavirus (HPV) at primary HPV cervical screening: A qualitative exploration of women’s information needs and preferences for communication of results

Abstract: Human Papillomavirus (HPV) primary cervical screening was implemented across England during 2019, where cervical cell samples are first tested for HPV and cytology is used to triage HPV-positive results. Around 8.5% of women who attend test HPV-positive with normal cytology (HPV+/normal). We aimed to explore women’s information needs and suggestions for improvements to result communication following an HPV+/normal result, among those with higher and lower levels of education. In‐depth interviews were conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…49 The impact of inadequate communication and education on widening inequalities was of concern in our review and the reality of this has been demonstrated by cervical screening changes, as less educated women demonstrated poorer understanding, indicating that inferior communication can exacerbate existing inequalities. 50,51 Overall, this suggests that future communication of changes to cancer screening programmes should provide transparent evidence and reassurance in public communications.…”
Section: Communication Preferencesmentioning
confidence: 99%
“…49 The impact of inadequate communication and education on widening inequalities was of concern in our review and the reality of this has been demonstrated by cervical screening changes, as less educated women demonstrated poorer understanding, indicating that inferior communication can exacerbate existing inequalities. 50,51 Overall, this suggests that future communication of changes to cancer screening programmes should provide transparent evidence and reassurance in public communications.…”
Section: Communication Preferencesmentioning
confidence: 99%
“…As with other studies, especially others, there is confusion about the source of infection, treatment, and reinfection. 17 , 20 When asked about related questions such as throat and rectal cancer and partner anxiety, women see HPV as more than just a cause of cervical cancer. Therefore, to reassure these women and meet the needs of these individuals, health care providers should consider appropriate counseling strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Even the mere positivity of a HPV test, often leads to stigmatization of the woman and blaming of the female sexual partner, or causes detrimental effects in the emotional aspects of sexual relationships. Moreover, the degree of understanding of the meaning of an HPV test result and of the related practical implications may be scarcely predictable, as successful communication is influenced also by individual education levels [ 48 ].…”
Section: Discussionmentioning
confidence: 99%